The Epiclesis debate at the council of Florence - Kappes, Christiaan W. (University of Notre Dame Press, 2019)
"The Epiclesis Debate at the Council of Florence is the first in-depth investigation into both the Greek and the Latin sides of the debate about the moment of Eucharistic transubstantiation at the Council of Florence. Christiaan Kappes examines the life and times of the central figures of the debate, Mark Eugenicus and John Torquemada, and assesses their doctrinal authority. Kappes presents a patristic and Scholastic analysis of Torquemada's Florentine writings, revealing heretofore-unknown features of the debate and the full background to its treatises. The most important feature of the investigation involves Eugenicus. Kappes investigates his theological method and sources for the first time to give an accurate appraisal of the strength of Mark's theological positions in the context of his own time and contemporary methods. The investigation into both traditions allows for an informed evaluation of more recent developments in the official teaching of the Roman Catholic Church in light of these historical sources. Kappes provides a historically contextual and contemporary proposal for solutions to the former impasse in light of the principles rediscovered within Eugenicus's works. This monograph speaks to contemporary theological debates surrounding transubstantiation and related theological matters, and provides a historical framework to understand these debates. The Epiclesis Debate at the Council of Florence will interest specialists in theology, especially those with a background in and familiarity with the council and related historical themes, and is essential for any ecumenical library"--